The Impact of Language in Eradicating the Menace of Rape Against the Girl Child in Lagos State - Obadare Felicia Tomi (Asshika: Journal of English Language Teaching and Learning, 2025)
This study explores the impact of language in eradicating the menace of rape against the girl child. Utilizing qualitative method, the research investigates how linguistic strategies in education, media, and policy can contribute to changing societal attitudes and reducing incidences of sexual violence. The study employed a descriptive research design of the survey type. The survey included a total of 100 respondents, consisting of 60 students from secondary schools, 10 teachers and educators, 15 media workers, and 15 policymakers and law enforcement officials. The study employed a simple random sampling technique to select the participants. The questionnaire, tagged "Language and Eradication of Rape Menace (LERM)," was created for the study and then tested for validity and reliability. The findings of the study revealed the importance of inclusive and empowering language, the role of media in shaping public perception, and the necessity of policy frameworks that emphasize protective and rehabilitative measures. The study recommends the integration of comprehensive sex education that employs inclusive and powerful language. Also, it recommends the adoption of criteria to ensure sensitive and respectful reporting on sexual abuse, along with their enforcement.